2017
DOI: 10.1016/j.ygyno.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to delivery and effectiveness of adjuvant radiation therapy in elderly patients with node-positive vulvar cancer

Abstract: Objective To examine adjuvant radiation therapy (RT) use, patterns of RT delivery, and clinical outcomes in older patients with node-positive vulvar cancer. Methods Using SEER-Medicare linked data, we identified 444 patients (age≥66 years) with node-positive squamous cell vulvar carcinoma, without distant metastases, and treated with primary surgery between 1991 and 2009. We used claims to examine RT use and the following delivery metrics: 1) completion of ≥20 fractions, 2) treatment duration <8 weeks, 3) <1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 26 publications
(30 reference statements)
1
16
0
Order By: Relevance
“…Adjuvant radiotherapy has been confirmed to improve outcomes in patients with node-positive vulvar SCC in previous research ( 16 – 19 ). A total of 69.7% of the patients in our study underwent adjuvant radiotherapy; however, adjuvant radiotherapy had no effect on survival outcomes of patients, according to the results of multivariate analyses.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Adjuvant radiotherapy has been confirmed to improve outcomes in patients with node-positive vulvar SCC in previous research ( 16 – 19 ). A total of 69.7% of the patients in our study underwent adjuvant radiotherapy; however, adjuvant radiotherapy had no effect on survival outcomes of patients, according to the results of multivariate analyses.…”
Section: Discussionmentioning
confidence: 68%
“…Adjuvant radiotherapy was not an independent predictor in our multivariate analyses. However, several studies have indicated that adjuvant radiotherapy is associated with an improvement of outcomes in patients with node-positive vulvar SCC ( 16 – 19 ). Therefore, we further analyzed the effect of adjuvant radiotherapy on survival outcomes according to the number of RLNs.…”
Section: Resultsmentioning
confidence: 99%
“…Adjuvant RT was associated with improved OS over surgery alone in this cohort of older women (HR, 0.71; 95% CI, 0.57-0.88; P=.002) along with a trend toward improved cause-specific survival (HR, 0.79; 95% CI, 0.59-1.05; P=.11). 111 Parameters for RT delivery were important among this cohort; 3-year OS and cause-specific survival were significantly improved in patients who received ≥20 fractions (3-year OS: 34% vs 26%; P=.008, and 3-year cause-specific survival: 48% vs 37%; P=.03).…”
Section: Adjuvant Rt and Chemoradiationmentioning
confidence: 82%
“…In our study, most patients received only RT, which explains the relatively poor outcome. Cameron et al (13) observed a 24% 5-year OS following surgery and adjuvant RT. The median patient age of that study was 78 years, similar to our own, so the outcomes are comparable.…”
Section: Discussionmentioning
confidence: 99%
“…Moore DH et al reported that 4% of T3-T4 patients administered CRT have been recently shown to have a complete CR of the primary tumour (12). In surgery and radiation combination treatment, studies have reported a 3-to 4-year OS of 32%-64% (13)(14)(15). However, differences in therapy make it difficult to compare outcomes.…”
Section: Discussionmentioning
confidence: 99%